2016
DOI: 10.1016/j.cub.2016.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Declines in Wilderness Areas Undermine Global Environment Targets

Abstract: Humans have altered terrestrial ecosystems for millennia [1], yet wilderness areas still remain as vital refugia where natural ecological and evolutionary processes operate with minimal human disturbance [2-4], underpinning key regional- and planetary-scale functions [5, 6]. Despite the myriad values of wilderness areas-as critical strongholds for endangered biodiversity [7], for carbon storage and sequestration [8], for buffering and regulating local climates [9], and for supporting many of the world's most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
384
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 420 publications
(398 citation statements)
references
References 37 publications
9
384
0
5
Order By: Relevance
“…large areas geographically isolated from humans by natural geographical barriers or with very limited human presence, may provide ecological baselines close to a ‘natural’ status [2,26,28]. Indeed, wilderness areas are traditionally viewed as areas featuring exceptional concentrations of biodiversity and abundance [29], albeit potentially suffering from global changes in a near future [30]. …”
Section: Introductionmentioning
confidence: 99%
“…large areas geographically isolated from humans by natural geographical barriers or with very limited human presence, may provide ecological baselines close to a ‘natural’ status [2,26,28]. Indeed, wilderness areas are traditionally viewed as areas featuring exceptional concentrations of biodiversity and abundance [29], albeit potentially suffering from global changes in a near future [30]. …”
Section: Introductionmentioning
confidence: 99%
“…Tracts of ecologically intact wilderness have been lost across the globe; less than 25% of non-barren ice-free land remains free from anthropogenic use (Ellis and Ramankutty 2008;Venter et al 2016;Watson et al 2016a). Yet intact wilderness supports high levels of biodiversity (Gurd et al 2001;Pollock et al 2017), diverse communities (see Crooks 2002;Ferraz et al 2003;Gibson et al 2013), ecosystem services (Bala et al 2007), and processes such as fire regimes (Gill et al 2013;Stephens et al 2014).…”
Section: Principle 2: Represent Ecosystem Diversitymentioning
confidence: 99%
“…Human pressures on the environment have had profound detrimental impacts on species across the globe (Ceballos et al 2015; see Box S1). Even within Canada, a country with vast remaining wilderness and an international reputation for natural resources (Watson et al 2016a), human-dominated regions show extensive biodiversity loss (see Fig. 1; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant declines in the area of the globe defined as wilderness (Watson et al 2016), and wilderness mapping has highlighted the inadequacies of the extent of protected areas. It is because of these things that studies have reported on the state of the current law, and calls have been made for improved legislative protection for wilderness, wild areas (a term used by the EC) and wild land.…”
Section: Wild Land and Its Protection From Wind Farmsmentioning
confidence: 99%